Students’ Strategies in Answering the TOEFL Listening Test at UIN Datokarama Palu - Wulandari, Mawar; Amelia, Yuni; Afifah, Afifah (Linguistics and ELT Journal, 2025)
This study aims to determine the level of listening skill in TOEFL and the strategies used in answering TOEFL listening. Students sometimes struggle to understand spoken English, especially while taking the TOEFL test for the first time. Therefore, it is crucial to identify the strategies they use to overcome these challenges. This study used a mixed method and a sequential explanatory type. The participants were 30 eighth-semester English students from UIN Datokarama Palu. All students took a TOEFL test, and the eight students with the highest listening scores were chosen for interview. Data were collected by using semi-structured interview and analyzed thematically to identify the different types of listening tactics employed. The results showed that students used three primary categories of strategies: social-affective, cognitive, and metacognitive. Students are more likely to employ cognitive and metacognitive techniques than social-affective ones.  This study indicates that increasing awareness of listening strategies can help first-time test takers improve their TOEFL scores and reduce anxiety about listening comprehension. The results suggest that students could implement the strategies to enhance their listening scores.